The effect of wool staple length on the mineral content using the same sheep feeding regime - Szigeti, Erika; Kátai, János; Komlósi, István; Oláh, János; Szabó, Csaba (Acta Agraria Debreceniensis, 2017)
The wool of sheep is suitable to test the mineral supply; however, a number of factors could affect the results. The growth rate and length of staple can be very different according to season, physiological state and individual variation. These factors are likely to affect the quantity of minerals accumulated into the wool. Therefore, the purpose of this research was to examine whether there is a difference between the mineral content of wool nearly reached the full staple length and the freshly grown wool using the same feeding regime.10 Tsigai pregnant sheep have been selected randomly from the same farm. Wool samples were obtained from the withers, side and quarter with bended scissors. Samples were mineralized using nitric acid and hydrogen peroxide using ultrasonic cleaning unit. P, Ca, Mg, Na, S, Cu,Se and Zn content were determined by ICP-OES. Statistical analyses were carried out by SAS (SAS Institute Inc., Cary, NC) GLM procedure.Differences between means were tested by Tukey test. Significantly lower Ca, Na, P, Zn values were found in case of intensively grown wool. Sampling location did not affect the mineral content. Herd mineral supply was adequate. Our results suggest that intensively grown wool samples have to be used for mineral analyses.